Knowledge, attitude, practice, and salt intake on obesity-related hypertension among institutional older adults: a comparative cross-sectional study - Farapti, Farapti; Sari, Afifah Nurma; Furqonia, Annisaa Wulida; Nadhiroh, Siti Rahayu; Kalpana, Chinnappan Ambrose (Jurnal Ners, 2025)
Introduction:  This study aims to assess the differences in knowledge, attitudes, practices, and salt intake among older adults with and without OB-HT in an institutional setting. Methods: A comparative cross-sectional study was conducted among 50 older adults (25 with OB-HT and 25 controls) in a nursing home in Indonesia. A visual-based questionnaire assessed sodium knowledge and attitude. Salt taste sensitivity was evaluated using a ranked salt intensity test on chicken soup formulations with varying salt levels (0.612–1.125 g/100 mL), and salt preference was measured using a hedonic sensory test. Energy and sodium intake were estimated using a semi-quantitative food frequency questionnaire (SQ-FFQ). Statistical analysis included chi-square, t-test, and Mann-Whitney U test (p < 0.05). Results: There was no significant difference in sodium-related food knowledge; however, males had lower sodium knowledge scores (p = 0.029). Attitudes toward high-sodium foods differed significantly only among males (p = 0.023). Older adults with OB-HT exhibited significantly lower salt taste sensitivity, particularly among males (p = 0.043), and demonstrated a stronger preference for higher sodium concentrations in food (p = 0.046). Notably, sodium intake differed only among females (p = 0.047). Conclusions: This study highlighted the relationship between OB-HT and dietary habits, emphasizing the need to identify sex-specific differences in knowledge, attitudes, and practices regarding salt intake among older adults.